AN EXPLORATORY CASE STUDY ON OUTSOURCING PRACTICES AND GOVERNANCE MECHANISMS IN MAINTENANCE AND OPERATIONS: EVIDENCE FROM BHILAI STEEL PLANT - Panchbhai, Suresh Kumar; Shastri, Tripti; Bhattacharjee, Bishwajeet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this exploratory case study is to examine the outsourcing practices and governance mechanisms in maintenance and operations at Bhilai Steel Plant, one of India’s largest public-sector steel manufacturing units. The study aims to understand how the distinction between core-close and core-distant activities influences outsourcing decisions and how governance mechanisms, including supplier capability, contractual clarity, and performance monitoring, affect operational efficiency. Adopting a qualitative, case-based methodology, the research draws insights from existing internal practices, organizational reports, and industry literature without collecting primary data or applying statistical tools. The findings reveal that strategic outsourcing decisions at Bhilai Steel Plant are guided by operational criticality, vendor competence, and the need for robust governance frameworks. Core-distant tasks are more frequently outsourced, while core-close functions are retained in-house or governed under strict protocols to mitigate risk. This research contributes to the practical understanding of outsourcing in heavy industries and underscores the importance of tailored governance structures.